DAMPAK INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Doni Satria (Universitas Negeri Padang, 2012)
The long run relationship between inflation and economic growth has been recognized by macroeconomist in the last three decades. For developing countries inflation effect on economic growth is more supply side phenomena than demand side or economic fluctuation (Basu, 2000). On the other hand stable and low inflation rate in the long run will promote higher output growth. I found significance two way causality between inflation and growth in Indonesia. The result has shown a non linier causality relationship from inflation to economic growth using Indonesian annual data from 1981 to 2010. The data reveals there is long run non linier relationship between inflation and growth.